Deconstructing the nuclear family in Norwegian textbooks - Knudsen, Susanne V. (Educar em Revista, 2014)
In this article the author presents how Norwegian textbooks in the 1990s and later make the nuclear family the norm of living together. The textbooks are for the secondary school in the curricula subjects of natural Science and environmental studies, social studies and home economics. The nuclear family in the chosen textbooks consists of the biological two-sex model and the cultural and social two-gender model. Some texts show the eagerness to present more than the heterosexual family life, and opens up to homosexuality both as sexual and social behavior. Single living is given little space in the textbook.